Wheat Cost-Return Budget (W-F Rotation) in Western Kansas - Sartwelle III, James D.; O'Brien, Daniel M. (My University, 1996)
This publication contains information for a projected budget reflecting expected income and cost based on wheat-fallow rotation practices in western Kansas.
MF257_1996-10
Keywords: MF257; Economics; Crops; MF